Impact of COVID-19 pandemic on doctors’ clinical practice - Kulkarni, Naveen S; Neelakanth S Patil; Vishalakshi; Asha Bullappa; Shriyan, Hithashree; Mishra, Subhashree (Asian Journal of Medical Sciences, 2022)
Background: The pandemic of COVID-19 has affected doctors, nurses, patients, and people working in hospitals. Aims and Objectives: This study aims to study the trends in doctors’ clinical practice during COVID-19 pandemic. Materials and Methods: The study conducted at SDMCMS&H, Dharwad, includes questionnaire on the impact of COVID-19 pandemic on doctors’clinical practice. The experience of doctors between May 2020 and June 2021 working in SDM University is considered in this study. Results: The number of non-COVID patients in OPD and IPD has reduced. The time spent in clinical examination is reduced, reliability on investigations has increased. The use of telemedicine is increasing. Conclusion: The impact of COVID-19 on clinical practice and doctors is multifactorial.The doctors and other health care workers can modify the COVID-19 impact on clinical practice by continuing to deliver the services as during pre-pandemic.